Producing stateness: police work in Ghana - Beek, Jan (African social studies series, 2017)
The history of police work : travelling models -- The internal organisation of the police : movements and moral orders -- Dockets, police community and politics : bureaucratic order in the police -- Money, morals, and law at traffic checks : registers in police interactions -- Patrolling public spaces : relational stateness -- Criminal investigations : boundary work and boundary shifting -- Private security, vigilantes and neighbours : relating to other policing actors -- Three police officers : living bureaucratically -- Conclusion: Stateness as aura